Hubungan antara Hipertensi, Diabetes Melitus, dan Hiperkolesterolemia dengan Kejadian Stroke Iskemik - Andrytha Gicella Tamburian; Budi T Ratag; Jeini Ester Nelwan (Universitas Sam Ratulangi, 2020)
Stroke is a functional brain disorder in the form of paralysis of the nerves due to impaired blood flow in one part of the brain. Ischemic stroke is the flow of blood to the brain stops due to blood clots that block blood vessels. The incidence of ischemic stroke occurs between 70% - 85% of stroke events. The prevalence of stroke in Indonesia in 2013 was 7‰ and increased in 2018 to 10.9‰. Based on Riskesdas in 2018, North Sulawesi ranks third highest for stroke sufferers in Indonesia. This research purposes to determine the relationship between hypertension, diabetes mellitus, and hypercholesterolemia with the incidence of ischemic stroke at GMIM Pancaran Kasih General Hospital Manado. This research uses analytic observational study with case control design and using Chi-Square test. The population in this study were all outpatients who came for treatment at the Neurology Polyclinic of GMIM General Hospital Pancaran Kasih Manado. The total sample of the case and control group was 72 respondents. This study uses secondary data on medical record files using a checklist. The results showed that hypertension was associated with the incidence of ischemic stroke with the results of the chi-square test obtained p value = 1,000 (p> 0.05) and OR value = 1.24 (95% CI; 0.342 - 4.498). The conclusion of this study is that there is a relationship between hypertension and the incidence of ischemic stroke and there is no relationship between diabetes mellitus and hypercholesterolemia with ischemic stroke.